DESIGN OF BORED PILE FOUNDATION AND DIAPHRAGM WALL WITH GROUND ANCHOR SUPPORT IN INDONESIAN MUSEUM OF TRADITIONAL GAMES, CENTRAL JAKARTA - Qamilla, Nadia
Indonesian Museum of Traditional Games, that is located in Jalan Tanah Abang Timur, Gambir, Jakarta, designed to fulfill the aim in cultural education and preservation of traditional Indonesian games. This museum facilitates exhibition, education, curation, and commercial needs in an area of 6500 m2. Generally, structure work is divided into two parts, which are upper structure and lower structure. The lower structure is functioned to endure and transfer loads given by the upper structure to soil layer. This final project will be focused on designing foundation and soil retaining structures. A foundation system should be able to endure force or action produced by weight of structure material, earthquake, occupancy and its utilization, and natural events. This final project will contain the design stage and criteria of bored pile foundation below the main museum structure and basement which will give sufficient bearing capacity to endure the loads from upper structure and uplift force exerted by water pressure in soil. Axial bearing capacity is calculated in compression and pull-out condition. Lateral bearing capacity is calculated by LPILE with deflection criterias. Deflection and force acted on pile in group configuration will later be checked by GROUP. Bored pile design for the main museum structure comes with the output of four types of pile cap configurations. Pile diameter and length are 0,8 m and 25 m consecutively. Meanwhile for the basement, one type of pile cap has been designed with pile diameter and length of 0,8 m and 20 m consecutively. Longitudinal reinforcement design is done with PCACOL. Exvacation work on basement area is designed with a depth of 8,5 m which will be supported with a type of embedded wall, that is diaphragm wall. Prestressed ground anchor will also be planned to stabilise the diaphragm wall by transmitting an applied tensile load into the ground. Stability analysis will be done by PLAXIS 2D with hardening soil model. Diaphragm wall width and depth are designed to be 0,8 m and 25 m consecutively. Ground anchor will be attached in two layers with a depth of -3,5 m and -7 m below the surface.